Cytological features of uterine carcinosarcoma: A retrospective study of 20 cases with an emphasis on the usefulness of endometrial cytology. Issue 6 (1st February 2019) - Okano, Kimiaki; Ishida, Mitsuaki; Sandoh, Kaori; Mizokami, Tomomi; Kita, Masato; Okada, Hidetaka; Tsuta, Koji
Abstract : Background: Carcinosarcoma of the endometrium is a relatively rare but aggressive neoplasm. Endometrial cytological features of this type of tumor have been rarely reported. This study aimed to clarify the usefulness of endometrial cytological examination in the diagnosis of endometrial carcinosarcoma. Methods: Patients histopathologically diagnosed with endometrial carcinosarcoma who underwent preoperative endometrial or endocervical cytological examination were enrolled. The endometrial and/or endocervical specimens were conventionally stained with Papanicolaou stain, and the cytological characteristics, including arrangement and shape of the neoplastic cells, and the nuclear and cytoplasmic features were reviewed. Results: Twenty patients were enrolled in the study. In the endometrial specimens, carcinomatous component was detected in almost all cases (94.4%), including those suspicious of carcinoma despite a small volume of carcinomatous cells. Sarcomatous component was observed in 6 of 18 cases (33.3%) and was significantly more frequently detected in the heterologous type (5 of 9 cases) compared to the homologous type (1 of 9 cases) ( P  = 0.046). In the endocervical specimens, carcinomatous component was present in 76.5% of cases, but sarcomatous component was detected in only 17.6% of cases. Conclusion: Although endocervical cytology can detect the carcinomatous component in more than 50% of endometrial carcinosarcoma cases, it has lesser capability to detect sarcomatous component. In conclusion, endometrial cytological examination is a more useful and accurate method to detect sarcomatous component of endometrial carcinosarcoma, particularly in the heterologous type, compared to endocervical cytological examination.